Molecular Characterization of a Multiethnic Group of 21 Patients with Type 3 von Willebrand Disease - Baronciani, Luciano; Cozzi, Giovanna; Canciani, Maria Teresa; Peyvandi, Flora; Srivastava, Alok; Federici, Augusto Bramante; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2000)
Type 3 von Willebrand disease is a rare autosomal disorder characterized by unmeasurable levels of von Willebrand factor and severe hemorrhagic symptoms. We studied a multiethnic group of 37 patients, from Italy (n = 14), Iran (n = 10) and India (n = 13) to identify the molecular defects and to evaluate genetic heterogeneity among these populations. Twenty-one patients (6 Italians, 9 Iranians and 6 Indians) were fully characterized at the molecular level. Twenty-four different gene alterations were identified, 20 of which have not been described previously. The majority of the mutations caused null alleles, 11 being nonsense mutations (Q218*, W222*, R365*, R373*, E644*, Q706*, S1338*, Q1346*, Y1542*, R1659*, E2129*), 4 small deletions (437delG, 2680delC, 6431delT, del 8491-8499), 3 possible splice site mutations [IVS9(-1)g→a, IVS29(+10)c→t, IVS40(-1)g → c], 3 candidate missense mutations (C275S, C2174G, C2804Y), 2 small insertions (7375insC, 7921insC) and 1 large gene deletion. The latter mutation was associated with the development of alloantibodies to VWF, but this complication was also found in a patient homozygous for a nonsense mutation (Q1346*). Due to the ethnic origin of the patients most of them were the offspring of consanguineous marriages and so were homozygous for the mutations found (18/21). Our results indicate that molecular defects responsible for type 3 VWD are scattered throughout the entire VWF gene (from exon 3 to 52), and that there is no prevalent and common gene defect in the three populations studied by us.
Keywords: von Willebrand factor; type 3 von Willebrand disease; gene analysis; mutation